Beastly Journeys Travel and Transformation at the fin de siècle - Youngs, Tim (Liverpool University Press, 2013)
A critical exploration of travel, animals and shape-changing in fin de siècle literature. Bats, beetles, wolves, butterflies, bulls, panthers, apes, leopards and spiders are among the countless creatures that crowd the pages of literature of the late nineteenth century. Whether in Gothic novels, science fiction, fantasy, fairy tales, journalism, political discourse, realism or naturalism, the line between the human and the animal becomes blurred. Beastly Journeys examines these bestial transformations across a range of well-known and less familiar texts and shows how they are provoked not only by the mutations of Darwinism but by social and economic shifts that have been lost in retellings and readings of them.